2006
DOI: 10.1107/s0108768106038869
|View full text |Cite
|
Sign up to set email alerts
|

Structure of strontium barium niobate Sr x Ba1 − x Nb2O6 (SBN) in the composition range 0.32 ≤ x ≤ 0.82

Abstract: The structure of strontium barium niobate crystals SrxBa1-xNb2O6 is comprehensively studied in the whole range of the tetragonal tungsten bronze phase (x=0.32-0.82) using both powder and single-crystal X-ray diffraction measurements. Unit-cell parameters, density, site-occupancy factors and interionic distances show an explicit composition dependence which can be consistently explained using simple model calculations. The temperature dependence of the unit-cell parameters exhibits a remarkable anisotropy in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
80
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 16 publications
14
80
0
2
Order By: Relevance
“…Intuitively, the larger ionic radius of Ba 2+ relative to Sr 2+ and Pb 2+ implies that the former will preferentially occupy the larger pentagonal sites, which has also been found experimentally. 6,18 However, even this simple effect of atomic size is not obvious: Large cations preferentially occupy the larger octahedral sites in 4-2 spinels, while the opposite is actually true for 2-3 spinels. 16 There is therefore no guarantee that a simple argument based on atomic size also holds for a different crystal structure such as the TTB-type.…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, the larger ionic radius of Ba 2+ relative to Sr 2+ and Pb 2+ implies that the former will preferentially occupy the larger pentagonal sites, which has also been found experimentally. 6,18 However, even this simple effect of atomic size is not obvious: Large cations preferentially occupy the larger octahedral sites in 4-2 spinels, while the opposite is actually true for 2-3 spinels. 16 There is therefore no guarantee that a simple argument based on atomic size also holds for a different crystal structure such as the TTB-type.…”
Section: Introductionmentioning
confidence: 99%
“…The high values of the spontaneous polarization and the electro-optic coefficient of SBN, especially for Sr-rich alloys, are affected by the smaller lattice parameters in comparison to other TTB ferroelectrics [13]. Upon heating from room temperature, SBN undergoes a ferroelectric phase transition from 4mm to 4/mmm [5].…”
mentioning
confidence: 99%
“…These may be discussed on the basis of the site occupancy. In a previous study, it has been shown that CBN28 and SBN61 have a similar unit-cell size [13,28]. On the other hand, the Ca 2+ ion radius is 1/ s [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the available structural [21] and dielectric data for related materials [22] one can suppose that the determined values of the relaxation time and the activation energy E a would be related to the collective oscillations of the short strong and long weak Nb-O bonds in the two different type corner-sharing NbO 6 octahedra aligned along c-axis.…”
Section: Resultsmentioning
confidence: 99%